Clínica psicanalítica: a debilidade mental em questão - Sanches, Daniele Rosa (2008)
The mental debility is a clinical category which is distinctly defined by two actuations fields: the medicine and the psychoanalysis. From the medical point of view the mental debility concerns to the lowest mental retard level. Mentals retardations are classified in according with results obtained in IQ tests. The differents measures classify the degrees of retardation with variations from light to serious level. The light retardation (mental debility) refers to IQ level between 50 and 70. From the medical point of view the retardation is understood as a pathology of intelligence. On the other hand for psychoanalysis, the mental debility is understood as a psychic position adopted by the subject of the unconscious. On the psychoanalysis concept the mental debility is not a pathology of the intelligence, but a psychopathology explicitated by the subject that doesn t appropriate what says neither what desires. On the psychoanalytic field, the mental debility refers to a subject completely under someone else s requires. This paper emphasizes on the importance for the psychoanalysis to make a mental debility diagnosis through the clinical listening